2018
DOI: 10.1002/ange.201804183
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐Based Lewis Acids Derived from Phosphonium Diazo Cations

Abstract: Reaction of PPh3 and [(p‐ClC6H4)N2][BF4] affords [(p‐ClC6H4)N(PPh3)N(PPh3)][BF4] 1, while reaction with (Ph2PCH2)2 gave [(p‐ClC6H4)(NPh2PCH2)2)][BF4] 2. These species confirm the Lewis acidity of [(p‐ClC6H4)N2(PR3)][BF4] cations at N. In contrast, use of bulky phosphines afford the species [ArN2(PR3)][BF4] (R=tBu 3, Mes 4). Compound 3 undergoes one electron reduction to give the stable radical [(p‐ClC6H4)N2(PtBu3)]. 5. Combination of 3 and PtBu3 acts as an FLP to effect (SPh)2 cleavage, generating [PhSPtBu3]+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 39 publications
(19 reference statements)
0
6
0
Order By: Relevance
“… 8 Important exceptions are “frustrated radical pairs”, which activate substrates via single electron pathways. 9 Recently, the range of LAs displaying FLP-like reactivity has expanded to encompass a number of cationic species (or neutral species that act as surrogates for the active cationic LA) based on B(III), 10 Si(IV), 11 C(IV), 12 N(III), 13 P(V), 14 and Sb(V). 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“… 8 Important exceptions are “frustrated radical pairs”, which activate substrates via single electron pathways. 9 Recently, the range of LAs displaying FLP-like reactivity has expanded to encompass a number of cationic species (or neutral species that act as surrogates for the active cationic LA) based on B(III), 10 Si(IV), 11 C(IV), 12 N(III), 13 P(V), 14 and Sb(V). 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, N‐based Lewis acids derived from diazonium cations are also explored [72] when Stephan and coworkers performed a reaction between diazonium salt [(p‐ClC 6 H 4 )N 2 ][BF 4 ] with one equivalent of base PR 3 (R=Ph, tBu, Mes) (Scheme 28). The resulting phosphonium diazo salts act as one electron acceptors.…”
Section: Nitrogen‐based Lewis Acidsmentioning
confidence: 99%
“…The high tuneability of the diazonium salt directly relates to the color of the azophosphonium salt, which can be substantiated by UV/Vis spectroscopy, revealing two absorption bands from  abs = 303-464 nm (→*) and  abs = 453-523 nm (n→*). 33 Further reaction of [(p-Cl-C 6 H 4 )N 2 (PMes 3 )][BF 4 ] with addition of 1 equivalent of tBu 3 P resulted in the liberation of Mes 3 P and showed clean addition of tBu 3 P, presumably because of the greater Lewis basicity of the latter. Note, addition of 1 equivalent of the less bulky Ph 3 P leads to the unstable species [(p-R-C 6 H 4 )N 2 (PPh 3 )][BF 4 ] (R = H, 32 Cl 33 ) and, upon addition of 2 equivalents, bis-addition is observed, resulting in the addition of the phosphine to both nitrogen atoms in a pseudotransoid disposition forming [(p-Cl-C 6 H 4 )N(PPh 3 )N(PPh 3 )][BF 4 ], 33 highlighting the necessity of bulky groups on the phosphine for controlled mono-addition.…”
Section: Figure 2 Examples Of Azophosphonium Saltsmentioning
confidence: 99%
“…Stephan and co-workers demonstrated that the formed azophosphonium salt could be used in follow-up chemistry forming a radical species (Scheme 19). 33 Dissolving the azophosphonium salt 30 with tBu 3 P in CH 2 Cl 2 gave an immediate color change of the solution to dark-red/brown upon addition of diphenyl disulfide. EPR spectroscopy indicated the formation of a paramagnetic species 31 [(p-Cl-C 6 H 4 )N 2 (Pt-Bu 3 )] • , which could also be formed by reacting the azophosphonium salt directly with PhSNa, potassium metal or Cp 2 -Co.…”
Section: Azophosphonium Salt As Radical Speciesmentioning
confidence: 99%
See 1 more Smart Citation